THE DYNAMIC CORRELATION BETWEEN OIL PRICES AND THE INDONESIAN OIL COMPANIES’ STOCK PRICE - Potto, Otniel Syebastian Agusto; Robiyanto, Robiyanto (Universitas Pendidikan Indonesia, 2021)
This study aims to analyze the correlation between oil prices and the Indonesian oil companies’ stock price during the pandemic of COVID-19 by testing the effect of oil price changes on companies' stock return and stock volatility. Also, by considering the dynamic correlation between oil prices and the Indonesian oil companies’ stock prices. The data were collected from secondary data at www.finance.yahoo.com, Oil prices, and the Indonesian oil companies’ stock price period from January 2020 to June 2020 during the pandemic of COVID-19. Further, the data were analyzed by using a GARCH method to examine the effect of changes in oil prices for stock return and stock volatility. Also, the DCC-GARCH method was used to see the dynamic correlation between oil prices and the Indonesian oil companies’ stock price. The result showed that changes in oil prices have a significant effect on stock price volatility and the presence of a positive dynamic correlation between oil prices and the Indonesian oil companies’ stock price. This research can be used as a reference for investors for their investments by looking at the relationship between the oil price and The Indonesian oil companies’ stock price.